Reconstructing Didactic Paradigms through Collaborative Knowledge Practices - Ahmad Zainuddin; Nur Aisyah Zainal (CV JK Riset Publishing Group, 2026)
This study investigates the reconstruction of didactic paradigms through collaborative knowledge practices in Indonesian higher education institutions undergoing pedagogical transformation. The research background centers on the inadequacy of transmission-oriented didactics in preparing graduates for collaborative and knowledge-intensive professional environments. Employing a qualitative phenomenological approach, data were collected from 28 participants across four universities through in-depth interviews, classroom observations, and reflective journals over ten months. Findings reveal three principal dimensions of paradigm reconstruction: the emergence of dialogic authority, the co-construction of disciplinary knowledge, and the development of epistemic agency among learners. The study concludes that meaningful reconstruction of didactic paradigms requires simultaneous shifts in educator identity, institutional culture, and assessment philosophy. These findings contribute theoretical and practical insights for curriculum designers, educational policymakers, and teacher educators committed to advancing collaborative and transformative learning cultures.